2010
DOI: 10.1093/bja/aeq046
|View full text |Cite
|
Sign up to set email alerts
|

Liver trauma secondary to ultrasound-guided transversus abdominis plane block

Abstract: The effect of the first EBP waned and a second EBP was performed about 42 days later. A larger blood volume (35 ml) was injected, and the patient was maintained in a head-down position for 20 min. Within a couple of hours, he became more alert and there was marked improvement in his social behaviour. This improvement was not as marked as that following the first EBP and lasted for ,1 month. A repeat MRI of the brain did not show any CSF leak. At the request of the neurologist and the family, a third and final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(71 citation statements)
references
References 4 publications
0
68
0
3
Order By: Relevance
“…Following the more widespread application of ultrasound for assisting nerve block techniques, the TAP block has been Potential complications include organ damage and local systemic toxicity due to the relatively large injection volume used in this procedure [52,53].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%
“…Following the more widespread application of ultrasound for assisting nerve block techniques, the TAP block has been Potential complications include organ damage and local systemic toxicity due to the relatively large injection volume used in this procedure [52,53].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%
“…Since the development of ultrasound guided technique no organ injuries have been reported while the procedure [42] except one case of liver injury which was said due to the result of excessive depth of penetration due to failure to accurately image the entire needle during the procedure [43]. Farooq et al [44] also reported a case of liver injury while using the Landmark based technique.…”
Section: Complications Of Tap Blockmentioning
confidence: 99%
“…49 Other technical variants include a 'multiple injection' Figure 6 Mean length of hospital stay technique and continuous infusion via a subcutaneous catheter. [50][51][52] The landmark technique, albeit running a marginally higher risk of significant visceral injury, 53,54 blocks the T7 and T8 dermatomes more reliably than ultrasonography guided blocks, 22,49 perhaps reflecting sites of injection. 55 Posteromedial spread outside the TAP has also been hypothesised to possibly affect visceral afferents, a property that might prove particularly useful in colorectal surgery.…”
Section: Addition Of Transversus Abdominis Plane Block To Patient Conmentioning
confidence: 99%